Market Making by Price-Setting Firms - Spulber, D. F. (Review of Economic Studies, 1996)
A model of market making by firms with heterogeneous consumers, suppliers and price-setting intermediaries is examined. Consumers and suppliers engage in time-consuming search for the best price and discount future returns. There exists a unique symmetric equilibrium pricing strategy. In equilibrium, there are non-degenerate distributions of ask and bid prices that straddle the Walrasian price. As the discount rate goes to zero, the ranges of the bid and ask prices, and the total output approach the Walrasian equilibrium values. As the discount rate becomes large, the ask and bid prices approach the monopoly pricing policies. An increase in the discount rate leads to an increase in the equilibrium number of active firms, profit per firm, the mean spread between ask and bid prices, and the variance of ask and bid prices, while lowering the number of active consumers and suppliers. The model is extended to examine the steady-state market equilibrium with continual entry and exit of consumers and suppliers.